High-quality forage production under salinity by using a salt-tolerant AtNXH1-expressing transgenic alfalfa combined with a natural stress-resistant nitrogen-fixing bacterium - Stritzler, Margarita; Pagano, Elba Maria; Berini, Carolina Andrea; Gomez, Maria Cristina; Ayub, Nicolás Daniel; Soto, Gabriela Cinthia (Elsevier, 2018)
Alfalfa, usually known as the “Queen of Forages”, is the main source of vegetable protein to meat and milk production systems worldwide. This legume is extremely rich in proteins due to its highly efficient symbiotic association with nitrogen-fixing strains. In the last years, alfalfa culture has been displaced to saline environments by other important crops, including major cereals, a fact that has reduced its biomass production and symbiotic nitrogen fixation. In this short communication, we report the high forage production and nutrient quality of alfalfa under saline conditions by alfalfa transformation with the AtNHX1 Na+/H+ antiporter and inoculation with the stress-resistant nitrogen-fixing strain Sinorhizobium meliloti B401. Therefore, the incorporation of transgenic traits into salt-sensitive legumes in association with the inoculation with natural stress-resistant isolates could be a robust approach to improve the productivity and quality of these important nitrogen-fixing crops